Blockchain adoption factors - Carlos Bernardino; Francisco Cesário; Carlos J. Costa; Manuela Aparicio; João Tiago Aparicio (International Journal of Information Systems and Project Management)
Blockchain technology is a distributed ledger that promises transformative changes across various sectors, yet its adoption and integrations in small and medium-sized organizations remain limited. This study investigates the factors that influence the adoption of blockchain technology, emphasizing the significance of Trust and Security as key moderators. Using a questionnaire distributed to a diverse group of employees and analyzing responses through Structural Equation Modeling (SEM-PLS), we constructed a predictive model of blockchain adoption. Our analysis reveals that Performance Expectancy and Social Influence positively affect the intention to adopt blockchain, indicating that perceived effectiveness and peer support drive adoption. Trust significantly enhances this intention, underscoring the importance of confidence in the technology's reliability and security. Environmental Concerns present a barrier, suggesting sustainability perceptions can deter adoption. This study conclusively demonstrates that promoting trust, addressing environmental sustainability, and leveraging social influence are pivotal for accelerating blockchain adoption in small and medium-sized organizations.